THE EVALUATION OF PHYSICAL DEVELOPMENT OF SCHOOLGIRLS OF ST. PETERSBURG WITH THE USE OF THE INTERNATIONAL STANDARDS - Грицинская, Вера Людвиговна; Гладкая, Валентина Сергеевна (Mother and Baby in Kuzbass, 2018)
The goal is to examine current trends in the growth and development of children and adolescents of schoolgirls of St. Petersburg.Material and methods the surveyed 2982 schoolgirls aged 7 to 17 years, pupils of educational institutions of St. Petersburg. The survey consisted of somatometry (measurement of length and body mass) and an assessment of the level and harmonious physical development, in accordance with the standards of the WHO («WHO Growth Reference 2007»). The level of physical development was assessed in accordance with the scale of Z-score for the length of the body; harmony in the centile scale for indicators of body mass index (BMI).The results of the surveyed students in all age groups was the mean values of body length (60,5-77,1 %) and the harmonious relationship of length and body mass (53,2-75,9 %). Set the asymmetry of indexes of length of body with a significant representation of students of above-average growth in all groups (14,6 % and 28,9 %). Also identified in the examined learners with the high level disharmonious weight and the ratio of body length (BMI index). Among the disharmonious variants of physical development in girls from age 7 to 16 years prevailed due to increased body mass (the 17,3-30,9 %). The exception was a seventeen year old girl, among them individuals with a high body mass were smaller (9,0 %) than students with insufficient weight (15,1 %). Of particular concern is the high prevalence of obesity in girls aged 7 to 15 years (6,6 % to 21,3 %). The high school prevalence of obesity is significantly lower than pupils of elementary grades (p < 0,001 ÷ p = 0,05), probably due to the craze of girls restrictive diets.Conclusions. The necessity of development of complex prevention programmers’ to promote a healthy lifestyle, rational nutrition and increase physical activity of the younger generation. The conclusion about the priority of the development and use of regional standards for the length of the body.
Keywords: physical development; children; schoolgirls